Réponses

  • Utilisateur Brainly
2014-03-26T13:42:30+01:00
On développe:

A= (2x-5) (3+x) 
A= 6x + 2x² -15 -5x
A= 2x² +x -15

B= (-1+x) (-2-x)
B= 2 +x -2x -x²
B= -x² -x +2

C= (3x+4) (2x+9) + (4x+2) (3x+6) 
C= 6x² + 27x + 8x + 36 + 12x² + 24x + 6x +12
C= 18x² + 65x + 48

D= (5x-3) (2x+3) - (x+2) (5-x)
D= 10x² + 15x -6x -9 - (5x -x² +10 -2x)
D= 10x² + 9x -9 +x² -3x -10
D= 11x² + 6x -19

E= (3x²+2x-5) (x+4)
E= 3x³ +12x² +2x² +8x -5x -20
E= 3x³ +14x² +3x -20 

Voilà ! J'espère t'avoir aidé(e) ! :)